2020
DOI: 10.1002/pon.5560
|View full text |Cite
|
Sign up to set email alerts
|

Mindfulness‐based arts interventions for cancer care: A systematic review of the effects on wellbeing and fatigue

Abstract: Objective Upon receiving a cancer diagnosis, life irrevocably changes and complex experiences of emotional distress often occur. There is a growing interest in mindfulness‐based arts interventions (MBAIs) to ameliorate the distress many patients experience. Our review objective was to synthesize the evidence on the effectiveness of MBAIs on psychological wellbeing and fatigue. Method Relevant quantitative articles were identified through a systematic search of the grey literature and online databases including… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 50 publications
(381 reference statements)
0
15
0
Order By: Relevance
“…For instance, many art museums have begun to offer mindfulness-oriented programs to benefit their visitors (e.g., Lehe & Stone, 2018). Psychology has developed several methods of cultivating mindfulness (e.g., see Lomas et al, 2019;Rieger et al, 2020;Taylor et al, 2021 for review) that can be adapted…”
Section: Discussionmentioning
confidence: 99%
“…For instance, many art museums have begun to offer mindfulness-oriented programs to benefit their visitors (e.g., Lehe & Stone, 2018). Psychology has developed several methods of cultivating mindfulness (e.g., see Lomas et al, 2019;Rieger et al, 2020;Taylor et al, 2021 for review) that can be adapted…”
Section: Discussionmentioning
confidence: 99%
“…Although there is little scientific evidence of MBAT as an intervention, it is slowly gaining recognition as a tool for improving psychosocial health. MBAT benefits include relief from anxiety, depression, fatigue, improvement in physical functioning, [11] psychological state, SWB, mindfulness, [12] and QoL. [11,12] Since in mindfulness and art-making, there is awareness away from the habitual thinking mind, toward heightened feeling and sense, it is suggested that both these processes promote the activation of the parasympathetic nervous system.…”
Section: Introductionmentioning
confidence: 99%
“…MBAT benefits include relief from anxiety, depression, fatigue, improvement in physical functioning, [11] psychological state, SWB, mindfulness, [12] and QoL. [11,12] Since in mindfulness and art-making, there is awareness away from the habitual thinking mind, toward heightened feeling and sense, it is suggested that both these processes promote the activation of the parasympathetic nervous system. [13] is induces a relaxation response and reduces psychological distress.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations